O processo de escolarização de estudantes com Transtorno do Espectro Autista – TEA - NERIS, Ana Cristina da Conceição (2024)
This article aims to reflect on the schooling process of students with Autism Spectrum Disorder (ASD). A bibliographical research was used based on Gil (2002). In the theoretical framework, we used studies by Cunha (2013), Kanner (1943), Camargo and Bosa (2009), Belisário (2010), among others. The results indicate that the lack of specific training on the part of teachers, in addition to structural needs, is one of the major barriers faced in the schooling process of students with ASD. Through the partnership between the family and the school, it contributes to the significant development of the child with ASD. Through this partnership, the teacher can base their practice considering the student's needs, based on the information collected from their guardians, which therefore contributes to the adaptation of pedagogical resources that will add to the learning process. We conclude that to obtain good results in the schooling of students with ASD, it is necessary that schools are adapted to the needs of students and, above all, the continued training of educators to enable the construction of effective pedagogical practices for students with autism,to help effectively, seeking to better understand your student and thus promote learning.